DINAMIKA GERAKAN MAHASISWA RIAU DI PEKANBARU PADA TAHUN 2010 – 2014 - Eko H. Marianto; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is intended to know and explain the condition of the movement of Riau Students in Pekanbaru especially especially in the period 2010-2014. So, this study does not want to condemn the poor orientation of the student movement, but wants to explore a pithy understanding surrounding the complexity of the student movement so that the debate is no longer around disorientation and stagnant student movement in the region. Because the student movement can not be compared against other student movements at certain times.The method used in this study is descriptive-kualiatif which directs the author to describe and describe the descriptive dynamics of Riau student movement in Pekanbaru in 2010-2014. In this case the researchers conducted interviews and analyzed theoretical books and popular books that explain the dynamics of student movement.Results of field research show that in the period 2010 - 2014, the Student movement experienced ups and downs. His condition illustrates that the student movement movement polarization occurs, and then marked by the issue of movement that tends to be partial. However, polarization should occur in the Riau student movement should be seen as its own dynamics and not as a threat. With the existing polarization, for example, it needs to build intensive communication in every issue of movement.Keywords: Student, Movement, Activist, Riau